On the oscillation of fractional-order delay differential equations with constant coefficients - Yaşar, Bolat (Elsevier BV, 2014)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Oscillation theory of functional-differential equations; delay differential equation; fractional-order differential equation; fractional-order derivative; oscillation; Functional-differential equations with fractional derivatives; 16. Peace & justice